Entrepreneurial Intelligence based on business motivation and developed using the Entrepreneurial Learning Model - Filda Rahmiati; Rendika Nugraha; Chong Mi An (JIE Scientific Journal on Research and Application of Industrial System, 2022)
The purpose of this study is to compare students' entrepreneurial intelligence between those who intend to be entrepreneurs and those who do not. This study employs a quantitative approach with a comparative technique. Through a google form, data were collected from 186 students as samples. The questionnaire is made up of questions pertaining to business motivation and business intelligence. The data were analyzed using the t-test to determine the difference between two groups. The findings of this study indicate that students who intend to become entrepreneurs have a greater level of entrepreneurial intelligence than those who do not.